2011
DOI: 10.1182/blood-2010-12-326298
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuing prophylactic transfusions increases the risk of silent brain infarction in children with sickle cell disease: data from STOP II

Abstract: In the STOP II trial, discontinuation of prophylactic transfusions in high risk children with sickle cell disease (SCD) resulted in a high rate of reversion to abnormal blood-flow velocities on transcranial Doppler (TCD) ultrasonography and strokes. We analyzed data from STOP II to determine the effect of discontinuing transfusions on the development or progression of silent brain infarcts on magnetic resonance imaging (MRI). At study entry, 21 of 79 (27%) patients had evidence of silent infarcts. There were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 36 publications
(45 reference statements)
0
44
0
Order By: Relevance
“…This is in accordance with the STOP II trial, which randomly assigned patients who had no evidence of stenosis and a history of abnormal intracranial velocities that had normalized on transfusion program to pursuing vs halting transfusions. 31 In the pursuing transfusion group, the number of SCI remained the same (n 5 25 vs 24), whereas the number of SCI increased from 27 to 45 in the transfusion-halted group. 31 Thus, current data suggest that transfusion program may be beneficial in preventing SCI occurrence in patients with a history of abnormal TCD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is in accordance with the STOP II trial, which randomly assigned patients who had no evidence of stenosis and a history of abnormal intracranial velocities that had normalized on transfusion program to pursuing vs halting transfusions. 31 In the pursuing transfusion group, the number of SCI remained the same (n 5 25 vs 24), whereas the number of SCI increased from 27 to 45 in the transfusion-halted group. 31 Thus, current data suggest that transfusion program may be beneficial in preventing SCI occurrence in patients with a history of abnormal TCD.…”
Section: Discussionmentioning
confidence: 95%
“…31 In the pursuing transfusion group, the number of SCI remained the same (n 5 25 vs 24), whereas the number of SCI increased from 27 to 45 in the transfusion-halted group. 31 Thus, current data suggest that transfusion program may be beneficial in preventing SCI occurrence in patients with a history of abnormal TCD. For patients with no abnormal intracranial velocities, the SIT Trial, which randomly assigned patients with SCI to transfusions vs simple observation, recently reported that transfusion program significantly reduced the incidence of SCI recurrence.…”
Section: Discussionmentioning
confidence: 95%
“…Among children with both abnormal TCD and silent infarcts, those who received transfusion therapy were significantly less likely to develop new silent infarcts [42]. A subset of those patients later had transfusions discontinued and demonstrated an increased frequency of progression of silent infarcts compared with those who continued transfusion therapy [112]. However, a recent study looking at transfusion in patients with overt stroke found progression of silent infarcts in 25% of subjects despite being optimally transfused [46].…”
Section: Secondary Stroke Preventionmentioning
confidence: 99%
“…14 Discontinuing transfusions on the STOP 2 trial was also associated with a higher occurrence of silent cerebral infarcts, documented in 3 of 37 patients (8.1%) in the continued-transfusion group compared with 11 of 40 (27.5%) in the transfusion-halted group. 15 Two ongoing randomized interventional trials aim to address current dilemmas regarding the use of chronic RBC transfusions to prevent neurologic complications in children with SCD. Comparison of hydroxyurea and transfusion therapy for children with abnormally elevated TCD velocities but no primary stroke is currently ongoing in the TCD with Transfusions Changing to Hydroxyurea (TWiTCH) trial (www.ClinicalTrials.gov identifier NCT01425307).…”
Section: Strokementioning
confidence: 99%